The power threshold of H-mode access in mixed hydrogen–tritium and pure tritium plasmas at JET with ITER-like wall. (1st August 2022) - Birkenmeier, G.; Solano, E.R.; Lerche, E.; Taylor, D.; Gallart, D.; Mantsinen, M.J.; Delabie, E.; Carvalho, I.S.; Carvalho, P.; Pawelec, E.; Hillesheim, J.C.; Parra Diaz, F.; et al.
Abstract: The heating power to access the high confinement mode (H-mode), P LH, scales approximately inversely with the isotope mass of the main ion plasma species as found in (protonic) hydrogen, deuterium and tritium plasmas in many fusion facilities over the last decades. In first dedicated L–H transition experiments at the Joint European Torus (JET) tokamak facility with the ITER-like wall (ILW), the power threshold, P LH, was studied systematically in plasmas of pure tritium and hydrogen–tritium mixtures at a magnetic field of 1.8 T and a plasma current of 1.7 MA in order to assess whether this scaling still holds in a metallic wall device. The measured power thresholds, P LH, in Ohmically heated tritium plasmas agree well with the expected isotope scaling for metallic walls and the lowest power threshold was found in Ohmic phases at low density. The measured power thresholds in ion cyclotron heated plasmas of pure tritium or hydrogen–tritium mixtures are significantly higher than the expected isotope mass scaling due to higher radiation levels. However, when the radiated power is taken into account, the ion cyclotron heated plasmas exhibit similar power thresholds as a neutral beam heated plasma, and are close to the scaling. The tritium plasmas in this study tended to higher electron heating fractions and, when heated with ion cyclotron waves, to relatively higher radiation fractions compared to other isotopes potentially impeding access to sustained H-modes.